Synthesis, Characterization, and Physicochemical Studies of Mixed Ligand Complexes of Inner Transition Metals with Lansoprazole and Cytosine - Sarika Verma; Sarita Shrivastva; Rashmi Shrivastva (Journal of Chemistry)
Few complexes of inner transition metals [Th(IV), Ce(IV), Nd(III), Gd(III)] have been synthesized by reacting their metal salts with lansoprazole, 2-([3-methyl-4-(2,2,2-trifluoroethoxy)pyridin-2-yl]methylsulfinyl)-1H-benzoimidazole and cytosine. All the complexes were synthesized in ethanolic medium. The yield percentage rangs from 80 to 90%. The complexes are coloured solids. The complexes were characterized through elemental analyses, conductance measurements, and spectroscopic methods (FT IR, FAB Mass, 1H NMR and UV). An IR spectrum indicates that the ligand behaves as bidentate ligands. The metal complexes have been screened for their antifungal activity towards Aspergillus niger fungi. The interaction of inner transition metals with lansoprazole, in presence of cytosine, has also been investigated potentiometrically at two different temperatures 26±1°C and 36±1°C and at 0.1 M (KNO3) ionic strength. The stability constants of ternary complexes indicate the stability order as Th(IV) < Ce(IV) < Gd(III) < Nd(III). logK values obtained are positive and suggest greater stabilization of ternary complexes. The values of thermodynamic parameters (free energy (ΔG), enthalpy (ΔH), and entropy (ΔS) are also calculated.